Censorship: Internet partially restored; social media still blocked (Bangladesh) - Voidly (Voidly Global Censorship Index, 2024)
CRITICAL severity censorship detected in Bangladesh. Data sourced from CensoredPlanet.
Censorship Incident ID: BD-2024-0001. Severity: critical. Confidence: 75%